2013
DOI: 10.1016/j.ijid.2013.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and mortality of pneumonia in adults in six Latin American countries

Abstract: Pneumonia is a common cause of hospitalization and mortality in adults in Latin America. Incidence increases substantially with increasing age, as does the likelihood of hospitalization and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 28 publications
2
30
0
6
Order By: Relevance
“…Our results showed a sex gap, with men presenting higher numbers of CAP hospitalizations, mortality and a higher risk of death during hospitalization. These results are in accordance with other studies that show a sex inequality in health indicators associated with hospitalizations [3,4,12,29], with men presenting consistently higher hospitalization rates for CAP, which may be related to a great number of risk factors, such as smoking, alcoholism, and exposure to toxic occupational exposure [3,29]. The greater ratio of male to female mortality may also reflect higher rates of smoking in males predisposing to respiratory disease [3,16].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results showed a sex gap, with men presenting higher numbers of CAP hospitalizations, mortality and a higher risk of death during hospitalization. These results are in accordance with other studies that show a sex inequality in health indicators associated with hospitalizations [3,4,12,29], with men presenting consistently higher hospitalization rates for CAP, which may be related to a great number of risk factors, such as smoking, alcoholism, and exposure to toxic occupational exposure [3,29]. The greater ratio of male to female mortality may also reflect higher rates of smoking in males predisposing to respiratory disease [3,16].…”
Section: Discussionsupporting
confidence: 90%
“…Despite many studies carried out, in Europe, it remains difficult to understand discrepancies between countries and geographic regions [4,[12][13][14][15][16]. The analyses of data from one or a few hospitals have the potential of introducing bias.…”
Section: Introductionmentioning
confidence: 99%
“…A study in Latin America (including Argentina, Paraguay and Uruguay) reported incidence varying between 4.8 and 110/10,000 person-years in people aged 18--64 years and 109-294/10,000 person-years in those over 65 years [11]. Another study in Latin America (Argentina, Brazil, Chile, Colombia, Mexico and Venezuela) reported CAP incidence varying between 32.6 and 80.4/10,000 personyears in a population over 50 years [12].…”
Section: Cap Incidencementioning
confidence: 99%
“…Venezuela tuvo una tasa de muerte de 35,1%, Brasil 20,9%, México 16,2%, Argentina 12,9%, Colombia 11,0 % y Chile 10,1%. La mayor parte de las muertes ocurrió en adultos sobre 75 años, representando 69,2% del total de fallecimientos 4 .…”
Section: Introductionunclassified